Attachment state of mind and trauma in mother and baby home adoptees. (March 2022) - Dalton, Natasha; McLaughlin, Marian; Cassidy, Tony
This study has two aims: to explore the experiences and impact of adoption among five adults (three males and two females, all over the age of 55) adopted from mother and baby homes in the UK and Ireland, and to establish each participant's state of mind (SOM) with regards to attachment using the Adult Attachment Interview (AAI) (George, Kaplan and Main, 1985–1996). It makes use of all information gained from the AAI by analysing the interview transcripts in two ways: (1) using the AAI scoring system (Main, Goldwyn and Hesse, 2003 ) to assess SOM; and (2) thematic analysis of the transcripts to produce an inductive set of themes. It was found that all participants had an insecure SOM with regards to attachment. For four out of the five participants, this was unresolved/disorganised, and the category 'preoccupied' was the most prevalent underlying three-way classification. Qualitative analysis of transcripts identified four overarching themes: (1) identity and belonging; (2) trauma; (3) 'silenced' coping; and (4) adverse parenting which reflected their experiences of adoption. The findings indicate that the participants were highly susceptible to trauma associated with loss. They also highlight the importance of suitable adoption placements and vetting of potential adopters. The clinical and research implications of the results and their contribution to the broader discussion of trauma related to adoption are discussed.